Algorithm Modified Ant Colony in Steel Production Scheduling - Imamah, Nurul; Mukhlash, Imam (Majalah Ilmiah Matematika dan Statistika, 2017)
Modified ant Colony algorithm is an extension of ant colony algorithm, it obtained based on observations of ant capabilities to sensing complex environments for search of food. In this paper will be reviewed the implementation modified ant colony alghorithm to the scheduling of steel production using 2 jobs 3 machines and 3 jobs 3 machines in the PT Hanil Jaya Steel using modified ant colony algorithm approach for minimization of makespan time from the whole jobs and at the end of the discussion in this thesis will study the implementation of modified ant colony algorithm in software.